IMPACT OF SELF-CONGRUITY AND BRAND IMAGE CONGRUITY ON BRAND LOYALTY: MEDIATING ROLE OF BRAND ATTITUDE - Ahmad, Najeeb; Aslam, Hassan Danial; Ayub, Arslan; Shabbir, Muhammad Farooq; Hafeez, Sadaf (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research paper was to investigate the impact of Self-Congruity (SC) and Brand Image Congruity (BIC) on Behavioural Loyalty (BL); to probe the mediation of Brand Attitude (BA) between Self Congruity and Brand Image Congruity and Behavioural Loyalty; to find out moderation effect of Reference Group (RG) on Brand Attitude and Behavioural Loyalty relationship. The data collected from 213 respondents through convenience sampling. Hypotheses were tested using regression analysis (SPSS 20). The result of the study indicated that all three types of Self-Congruity and Brand Image Congruity dimensions positively and significantly affected brand attitude. Brand Personality Congruity was the stronger predictor of a brand attitude than other tested predictors. The findings of the study provided several useful managerial implications. Manager more focused on self-congruity because customers focused on the brand personality and match it with their personalities and find resemblance with the particular brand. This research study contributed to the literature by examining the Brand Attitude as a mediator and Reference Group as a moderator.